PENGARUH LITERASI AGAMA ISLAM TERHADAP PRESTASI BELAJAR PAI DI SMK INSAN TEKNOKRAT BEKASI (Jaya Cimuning) - Jamiatul Maghfiroh; Acep Mulyadi; Rabiyannur Lubis (Turats, 2023)
This study aims to determine the effect of Islamic religious literacy on learning achievement inIslamic religious education at SMK Insan Technocrat Bekasi (Jaya Cimuning). This research is motivatedby low Islamic religious literacy in students, due to the world of technology which is developing veryrapidly, one of which is the lack of teacher strategies in applying Islamic religious literacy methods and inthe field of entertainment, the rise of students today prefers to play online games and watch entertainmenton television. Or smartphones that they have so that students' interest in reading and studying religionmore deeply is reduced. Reading is a window to the world, by getting used to reading students will gainknowledge and insight or students' mindsets will become critical, and deepen the Islamic religion amongteenagers or students at this time it is very necessary to become a guideline for akhlakul karimahaccording to the teachings of Islam applied in everyday life. This study uses quantitative researchmethods, and uses a survey research design with a correlational approach. The survey method is used toobtain data from certain natural places (not actions). Sampling in this study using simple randomsampling technique. The research subjects were students of class X, while the object of this research wasthe Islamic religious literacy method. The population in this study were 14 students of class X at SMKInsan Teknokrat Bekasi (Jaya Cimuning) both male and female. The data collection technique used is aquestionnaire or questionnaire with a rating scale of 1-5. The results of the study revealed that there wasa significant correlation between the influence of Islamic religious literacy and student achievement inPAI at SMK Teknokrat Bekasi. This is shown by the coefficient (R) of 0.725 and the R Square value(coefficient of determination) of 0.526 which indicates that Islamic education learning achievement (Y) isinfluenced by Islamic religious literacy (X) of 52.6%, the remaining factors another 47.4% which gave"the influence of Islamic Education Learning Achievement of students at SMK Insan Teknorat Bekasi(Jaya Cimuning).